AL-GHAZALI: REPUTASI DAN PENGARUHNYA DI PESANTREN - Ghozi Mubarok (Dirosat : Journal of Islamic Studies, 2016)
Al-Ghazali is a ulama who has more interest in knowledge, has more accurate and polemic arguments, and has more abilities in syntheses of impossible thing to correlated. It can be looked how al-Ghazali’s concept has role more important in Islamic boarding school of Indonesia, especially in fiqh, philosophy, Kalam and Sufism (tasauf). Even if al-Ghazali was just known in Islamic boarding school by Ihya’ Ulum ad-Din, but it was an encyclopedic and giving more explanations about Islamic knowledge, so the influences of al-Ghazali’s concept of this book (ihya’ ulum ad-Din) can be felt outside tasauf. This journal use content analyzing method, especially al-Ghazali’s book in detail of fiqh such as; al-Basith, al-Wasith, al-Wajiz and al-Khulashah. And also in principle of fiqh, such as; al-Mankhul and al-Mustashfa. Besides that, al-Ghazali wrote about philosophy which called by Maqasid al-Falasifah, Tahafut al-Falasifah and al-Munqidz min adh-Dhalal. In Kalam, al-Ghazali wrote some books; al-Iqtishad fi al-I’tiqad and Iljam al-‘Awwam ‘an ‘ilm al-Kalam. One of his monumental book in tasawuf is Ihya’ ‘Ulum ad-Din.